Crystallization and preliminary X‐ray crystallographic analysis of YfcM: an important factor for EF‐P hydroxylation. Issue 9 (1st September 2014) - Kobayashi, Kan; Suzuki, Takehiro; Dohmae, Naoshi; Ishitani, Ryuichiro; Nureki, Osamu
Abstract : Elongation factor P (EF‐P) plays an essential role in the translation of polyproline‐containing proteins in bacteria. It becomes functional by the post‐translational modification of its highly conserved lysine residue. It is first β‐lysylated by PoxA and then hydroxylated by YfcM. In this work, the YfcM protein from Escherichia coli was overexpressed, purified and crystallized. The crystal of YfcM was obtained by the in situ proteolysis crystallization method and diffracted X‐rays to 1.45 Å resolution. It belonged to space group C 2, with unit‐cell parameters a = 124.4, b = 37.0, c = 37.6 Å, β = 101.2°. The calculated Matthews coefficient ( V M ) of the crystal was 1.91 Å 3  Da −1, indicating that one YfcM molecule is present in the asymmetric unit with a solvent content of 35.7%.